2021
DOI: 10.3390/biomedicines9050544
|View full text |Cite
|
Sign up to set email alerts
|

Variants in Maternal Effect Genes and Relaxed Imprinting Control in a Special Placental Mesenchymal Dysplasia Case with Mild Trophoblast Hyperplasia

Abstract: Placental mesenchymal dysplasia (PMD) and partial hydatidiform mole (PHM) placentas share similar characteristics, such as placental overgrowth and grape-like placental tissues. Distinguishing PMD from PHM is critical because the former can result in normal birth, while the latter diagnosis will lead to artificial abortion. Aneuploidy and altered dosage of imprinted gene expression are implicated in the pathogenesis of PHM and also some of the PMD cases. Diandric triploidy is the main cause of PHM, whereas mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The PMD newborns with normal phenotype should be followed-up for BWS features of the mesenchymal tumor (hepatic mesenchymal hamartoma, congenital adrenal hyperplasia, and vascular hamartoma) [ 51 ]. Some cases of PMD are diagnosed in conjunction with mesenchymal hamartoma of the liver (MHL), while in others, the diagnosis is made after an MHL diagnosis [ 24 , 59 ]. MHL is a benign hepatic tumor characterized by excessive, focal growth of an admixture of epithelial and vascular components, which becomes multicystic as it enlarges, providing a poorer prognosis than for fetuses without structural anomalies (IUFD or neonatal death) [ 54 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PMD newborns with normal phenotype should be followed-up for BWS features of the mesenchymal tumor (hepatic mesenchymal hamartoma, congenital adrenal hyperplasia, and vascular hamartoma) [ 51 ]. Some cases of PMD are diagnosed in conjunction with mesenchymal hamartoma of the liver (MHL), while in others, the diagnosis is made after an MHL diagnosis [ 24 , 59 ]. MHL is a benign hepatic tumor characterized by excessive, focal growth of an admixture of epithelial and vascular components, which becomes multicystic as it enlarges, providing a poorer prognosis than for fetuses without structural anomalies (IUFD or neonatal death) [ 54 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The location of genes in the imprinted region was visualised for house mouse, human, cattle and tammar wallaby using the DNA Features Viewer library (Zulkower and Rosser 2020 ). ICR locations were from NCBI (Gene ID: 105317033, 105259599) or based on the position of published bisulfite primers (Smits et al 2008 ; Oh et al 2008 ; Robbins et al 2012 ; Wang et al 2015 ; Huang et al 2021 ). The position of KCNQ1OT1 in cattle and the tammar wallaby is from primer positions used to generate a short amplicon of the transcript (Ager et al 2007 ; Robbins et al 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several PMD cases composed entirely of biparental cells have also been reported [ 32 , 74 , 75 , 76 , 77 , 78 ]. Recently, we genotyped 25 macroscopic PMD specimens and found that 9 (36%) showed a normal biparental genotype [ 28 ].…”
Section: Etiologymentioning
confidence: 99%